2018
DOI: 10.1021/jacs.7b13620
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Thermosetting Epoxies Based on Fractionated and Well-Characterized Lignins

Abstract: Here we report the synthesis of thermosetting resins from low molar mass Kraft lignin fractions of high functionality, refined by solvent extraction. Such fractions were fully characterized by P NMR, 2D-HSQC NMR, SEC, and DSC in order to obtain a detailed description of the structures. Reactive oxirane moieties were introduced on the lignin backbone under mild reaction conditions and quantified by simpleH NMR analysis. The modified fractions were chemically cross-linked with a flexible polyether diamine ( M ≈ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
251
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(273 citation statements)
references
References 42 publications
20
251
1
1
Order By: Relevance
“…Decrease susceptibility to hydrolytic degradation 111,[113][114][115][116] Statistical design, 117 enzyme layer deposition, 119 amphiphilic battery binder, 121 seaweed 120,122 Lignin Increase reactivity to condensation reactions, 123,124 improve reproducibility and definition of structure 125 Vitrimer with reversible bonding 126…”
Section: Polysaccharides and Proteinsmentioning
confidence: 99%
“…Decrease susceptibility to hydrolytic degradation 111,[113][114][115][116] Statistical design, 117 enzyme layer deposition, 119 amphiphilic battery binder, 121 seaweed 120,122 Lignin Increase reactivity to condensation reactions, 123,124 improve reproducibility and definition of structure 125 Vitrimer with reversible bonding 126…”
Section: Polysaccharides and Proteinsmentioning
confidence: 99%
“…[11,12] For example, low molecular weight (MW) Kraft lignin fractions were shown to form thermosets with more optimal properties. [13] This was determined by first fractionating the bulk material taken directly from the industrial process using a selective dissolution protocol (see Figure 1D). Subsequent conversion of the selected fractions into the corresponding thermosets identified the best fraction to use.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high hydrophobicity, OL has been incorporated into different thermoplastic polymers, such as polyurethane and poly(ester‐amine) by crosslinking or grafting . It was found that the polyurethane foams produced with OL demonstrated a higher crosslinking density and thus better mechanical properties compared to that incorporated with KL, probably due to the better miscibility of OL in the polyol . Table also shows that lignosulphonate is considered to be a potential candidate for polymerization attributing to its larger amount of functional groups.…”
Section: Lignin Polymer Polymerizationmentioning
confidence: 53%
“…[65,77] It was found that the polyurethane foams produced with OL demonstrated a higher crosslinking density and thus better mechanical properties compared to that incorporated with KL, probably due to the better miscibility of OL in the polyol. [78,79] Table 5 also shows that lignosulphonate is considered to be a potential candidate for polymerization attributing to its larger amount of functional groups. As expected, few studies on the polymerization of HL have been reported due to its low reactivity.…”
Section: Lignin Polymer Polymerizationmentioning
confidence: 99%